Methanolic extracts of Solidago gigantea leaves as sustainable antifeedants against a stored pest: Sitophilus granaries - Bączek, Paulina; Łyczko, Jacek; Twardowska, Kamila (Journal of Plant Protection Research, 2026)
The development of natural insecticides is essential to minimize the adverse effects of synthetic plant protection products on the environment, human health, and non-target organisms. Natural bioactive compounds are considered safe, biodegradable, and often more selective, making them promising alternatives for sustainable pest management. Controlling insect pests in stored food products remains challenging due to restrictions on the use of chemical insecticides, which can leave harmful residues. Therefore, identification of plant-derived antifeedants is a viable solution. This study aimed to evaluate the antifeedant activity of methanolic leaf extracts from the invasive giant goldenrod (Solidago gigantea Aiton) against the grain weevil (Sitophilus granarius L.), a major storage pest. The chemical composition of the extracts was analyzed by LC-MS/MS, which identified 12 compounds. Chlorogenic acid, quercetin, and rutin were found at the highest concentrations, while citric acid, gallic acid, and kaempferol-3-rutinoside were present at the lowest concentrations. Antifeedant activity was assessed using the "wheat wafer test" at three extract concentrations (3.5, 5.0, and 12.0 mg⋅mL-1) dissolved in ethanol. The extracts demonstrated medium to good antifeedant activity against female grain weevils and weak to medium effects against males. A significant reduction in feeding was observed in most cases, depending on both the sex of the insect and the extract concentration. Methanolic leaf extracts of S. gigantea exhibited promising antifeedant properties and may serve as potential natural insect deterrents. Further studies are required to evaluate their efficacy, safety, and mode of action under storage and field conditions.